2016
DOI: 10.1007/s00467-016-3392-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and kidney disease: a bidirectional relationship

Abstract: Recent technological advances and efforts, including powerful metagenomic and metatranscriptomic analyses, have led to a tremendous growth in our understanding of microbial communities. Changes in microbial abundance or composition of human microbial communities impact human health or disease state. However, explorations into the mechanisms underlying host–microbe interactions in health and disease are still in their infancy. Although changes in the gut microbiota have been described in patients with kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 87 publications
(104 reference statements)
1
133
0
7
Order By: Relevance
“…Studies have also demonstrated the important role of intestinal dysbiosis in renal physiology and pathophysiology (22,23) such as accumulation of uremic toxins, systemic inflammation, and infection, which all may contribute to the development of CKD, its progression, and its complications (22,(24)(25)(26)(27)(28)(29). Restoration of microbiome diversity by administration of probiotics may provide beneficial effects on kidneys (25,(30)(31)(32)(33). This has been shown in uremic rats and kidney ischemia reperfusion injury models (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have also demonstrated the important role of intestinal dysbiosis in renal physiology and pathophysiology (22,23) such as accumulation of uremic toxins, systemic inflammation, and infection, which all may contribute to the development of CKD, its progression, and its complications (22,(24)(25)(26)(27)(28)(29). Restoration of microbiome diversity by administration of probiotics may provide beneficial effects on kidneys (25,(30)(31)(32)(33). This has been shown in uremic rats and kidney ischemia reperfusion injury models (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 98%
“…Intestinal dysbiosis, an imbalance between pathogenic and protective microbiota, has been associated with a variety of health conditions including Clostridium difficile (16,17), Crohn's disease (18,19), non-alcoholic steatohepatitis (NASH) (20), and systemic inflammation (21). Studies have also demonstrated the important role of intestinal dysbiosis in renal physiology and pathophysiology (22,23) such as accumulation of uremic toxins, systemic inflammation, and infection, which all may contribute to the development of CKD, its progression, and its complications (22,(24)(25)(26)(27)(28)(29). Restoration of microbiome diversity by administration of probiotics may provide beneficial effects on kidneys (25,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Kidney disease is associated with low fiber consumption and increased intestinal permeability due to a modified intestinal microbiota [5]. During obesity there is an inflammatory state and imbalance in the gut microbiota composition (dysbiosis) involving the toll-like receptor (TLR) family.…”
Section: Introductionmentioning
confidence: 99%
“…The adult gut is dominated by 2 bacterial phyla, the Gram-negative Bacteroides and the Gram-positive Firmicutes. The gut microbiota has a central role in the metabolism of dietary fibers, which are not degraded by human enzyme; furthermore, it plays a role in the stimulation of the immune system, maintenance of intestinal epithelium homeostasis, synthesis of vitamins, enhancement of gastrointestinal motility and function, production of short-chain fatty acids, and polyamines [39] . Also, the gastrointestinal system is the interface between the blood and the potentially toxic contents of the gut.…”
Section: Gut Microbiome As a Potential Source Of Uremic Toxinsmentioning
confidence: 99%